Problematika Penerapan Sanksi Pidana dalam Perkawinan Terhadap Poligami Ilegal - Jurna Petri Roszi (AL-ISTINBATH : Jurnal Hukum Islam, 2018)
This article aims to describe the problems of the application of criminal sanctions against polygamy committed illegally in the middle of society. Regardless of the controversy of agreeing and disagreeing, the issue of polygamy is a reality that occurs in society. The purpose of polygamy is the same as the purpose of marriage itself, that is worship. However, when the issue of marriage, that in is fact private law, violates the provisions, then the perpetrators may be subjected to criminal sanctions. Criminal sanctions imposed on illegal polygamists are very diverse. This is supported by the attitude of government's ambiguity in viewing illegal polygamy. The Government's doubt and uncertainty in viewing the illegal act of polygamy has implications for the inherent criminal sanctions against the act, strangely the criminal sanction inherent in the law depends on the degree to which the regulations are looked at. This research uses normative law research method whith normative juridical approach. The results of illegal polygamy research is not seen as overspel acts that can be threatened with criminal provisions Article 284 of the Criminal Code because the element of overspel is not the same as polygamy. Polygamy remains a legitimate marriage as the norms contained in the Law No.1 of 1974 onmarriage.Nevertheless the marriage of polygamy must still fulfill the terms and conditions as determined by the Law No.1 of 1974.